Perovskite photovoltaic cell, preparation method thereof and laminated cell
Patent Information
- Application Number
- CN202510532647.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2025-08-08
AI Technical Summary
[0005]本发明的目的在于提供一种钙钛矿光伏电池及其制备方法、叠层电池,以解决钙钛矿光伏电池的光电转化效率低的技术问题
Smart Images

Figure CN120456721A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photovoltaic technology, and in particular to a perovskite photovoltaic cell and a preparation method thereof, and a stacked cell. Background Art
[0002] The statements in this section merely provide background art related to the present invention and do not necessarily constitute prior art.
[0003] Perovskite photovoltaic cells (PSCs) are a new type of compound thin-film photovoltaic cell that utilizes perovskite-type materials as the light-absorbing layer. Interface defects or mismatches between the perovskite light-absorbing layer and adjacent layers are crucial to device performance. Hole transport layers (HTLs) and electron transport layers (ETLs) are typically placed on the upper and lower surfaces of the perovskite light-absorbing layer to reduce energy level mismatch and facilitate carrier transport, injection, or extraction.
[0004] In related technologies, the materials of the hole transport layer have problems such as difficulty in effectively improving the photoelectric conversion efficiency of perovskite photovoltaic cells. Summary of the Invention
[0005] The purpose of the present invention is to provide a perovskite photovoltaic cell and a preparation method thereof, and a stacked cell to solve the technical problem of low photoelectric conversion efficiency of perovskite photovoltaic cells.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] In a first aspect, the present invention provides a perovskite photovoltaic cell comprising a perovskite light-absorbing layer and a hole transport layer stacked on one side of the perovskite light-absorbing layer, wherein the hole transport layer comprises a hole transport material and a benzenesulfonate, wherein the hole transport material comprises one or more of nickel oxide, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid, and [6-(3,6-dimethoxy-9H-carbazole-9-yl)hexyl]phosphonic acid.
[0008] According to at least one embodiment of the present invention, the mass ratio of the hole transport material to the benzenesulfonate is 10:(0.05-0.1).
[0009] According to at least one embodiment of the present invention, the benzene sulfonate includes one or more of halogenated benzene sulfonates, alkylbenzene sulfonates, nitrogen-containing heterocyclic substituted benzene sulfonates, amino- and amine-substituted benzene sulfonates.
[0010] According to at least one embodiment of the present invention, the molecular weight of the benzenesulfonate salt is less than or equal to 2 kDa.
[0011] According to at least one embodiment of the present invention, the benzenesulfonate salt includes a sulfonic acid functional group containing a para-substituent on the benzene ring.
[0012] According to at least one embodiment of the present invention, the benzenesulfonate includes one or more of 4-chlorobenzenesulfonate, benzyl bromide p-toluenesulfonate, sodium 4-isopropylbenzenesulfonate, 2-amino-5-chlorobenzenesulfonic acid hydrochloride, 1-butyl-3-methylimidazole p-toluenesulfonate, and N-butylpyridinium sulfonate p-toluenesulfonate.
[0013] According to at least one embodiment of the present invention, the hole transport material includes nickel oxide, and the benzenesulfonate includes sodium 4-chlorobenzenesulfonate.
[0014] According to at least one embodiment of the present invention, the thickness of the hole transport layer ranges from 20 nm to 200 nm.
[0015] In a second aspect, the present invention further provides a stacked battery comprising a plurality of electrically connected photovoltaic cells, at least one of which is the photovoltaic cell described in the first aspect.
[0016] In a third aspect, the present invention further provides a method for preparing a perovskite photovoltaic cell, comprising:
[0017] providing a conductive substrate;
[0018] forming a hole transport layer on the conductive substrate, the hole transport layer comprising a hole transport material and a benzenesulfonate, wherein the hole transport material comprises one or more of nickel oxide, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid, and [6-(3,6-dimethoxy-9H-carbazole-9-yl)hexyl]phosphonic acid;
[0019] A perovskite light absorption layer, an electron transport layer and an electrode are sequentially formed on the hole transport layer to obtain the photovoltaic cell.
[0020] According to at least one embodiment of the present invention, the mass ratio of the hole transport material to the benzenesulfonate is 10:(0.05-0.1).
[0021] According to at least one embodiment of the present invention, the benzene sulfonate includes one or more of halogenated benzene sulfonates, alkylbenzene sulfonates, nitrogen-containing heterocyclic substituted benzene sulfonates, amino- and amine-substituted benzene sulfonates.
[0022] According to at least one embodiment of the present invention, the molecular weight of the benzenesulfonate salt is less than or equal to 2 kDa.
[0023] According to at least one embodiment of the present invention, the benzenesulfonate salt includes a sulfonic acid functional group containing a para-substituent on the benzene ring.
[0024] According to at least one embodiment of the present invention, the benzenesulfonate includes one or more of 4-chlorobenzenesulfonate, benzyl bromide p-toluenesulfonate, sodium 4-isopropylbenzenesulfonate, 2-amino-5-chlorobenzenesulfonic acid hydrochloride, 1-butyl-3-methylimidazole p-toluenesulfonate, and N-butylpyridinium sulfonate p-toluenesulfonate.
[0025] According to at least one embodiment of the present invention, forming a hole transport layer on a conductive substrate includes:
[0026] The hole transport material and benzenesulfonate are prepared into a solution and coated on the conductive substrate.
[0027] According to at least one embodiment of the present invention, the solution is coated on the conductive substrate by spin coating, the spin coating speed ranges from 1000 rpm to 4000 rpm, the spin coating time ranges from 10s to 30s; and / or,
[0028] The concentration of the solution ranges from 3 mg / mL to 15 mg / mL.
[0029] According to at least one embodiment of the present invention, after the solution is coated on the conductive substrate by a spin coating method, the preparation method further includes:
[0030] Annealing the conductive substrate coated with the solution, wherein the annealing temperature ranges from 120° C. to 180° C., and the annealing time ranges from 20 min to 40 min.
[0031] One or more technical solutions provided in the exemplary embodiments of the present invention can achieve at least one of the following beneficial effects.
[0032] The perovskite photovoltaic cell of an exemplary embodiment of the present invention includes a perovskite light-absorbing layer and a hole transport layer stacked on one side of the perovskite light-absorbing layer. Specifically, the hole transport layer is disposed between the perovskite light-absorbing layer and the conductive substrate, forming a trans-structured perovskite photovoltaic cell. The hole transport layer is formed from a hole transport material and benzenesulfonate molecules doped therein. Specifically, the hole transport material includes one or more of nickel oxide, [2-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethoxy-9H-carbazol-9-yl)butyl]phosphonic acid, and [6-(3,6-dimethoxy-9H-carbazol-9-yl)hexyl]phosphonic acid.
[0033] Compared to the prior art, which first uses a passivating agent to modify the upper surface of the perovskite light-absorbing layer or to modify the interface defects between the charge transport layer (electron transport layer and hole transport layer) and the perovskite light-absorbing layer to improve cell performance, the passivating agent typically binds to a single active binding site on the upper or lower surface of the perovskite light-absorbing layer, resulting in weak interfacial binding forces. Furthermore, these surface passivating agents typically form a dense vertical stack on the upper and lower surfaces of the perovskite light-absorbing layer, introducing unnecessary resistance between the perovskite light-absorbing layer and the charge transport layer, hindering carrier extraction and transport. The perovskite photovoltaic cell of the exemplary embodiment of the present invention uses a hole transport material doped with benzenesulfonate molecules to passivate the surface of the perovskite light-absorbing layer facing the hole transport layer, eliminating the need for the additional passivation step of the perovskite light-absorbing layer surface.
[0034] Because the benzenesulfonate molecule has a flat structure of benzene rings and sulfonic acid functional groups, it can be parallel to the surface of the perovskite light-absorbing layer. Compared with the vertically arranged structure formed by commonly used surface passivators, the interface resistance between the perovskite light-absorbing layer and the hole transport layer is lower. As a result, the conductivity of the hole transport layer is higher, which can better match the energy level of the perovskite light-absorbing layer and enhance the hole extraction efficiency.
[0035] Furthermore, compared to conventional surface passivators, which typically bind to a single active binding site on the surface of the perovskite light-absorbing layer, resulting in weak interfacial bonding, the sulfonic acid functional groups contained in the benzenesulfonate molecules in the hole transport layer of the exemplary embodiment of the present invention anchor to multiple Pb sites on the surface of the perovskite light-absorbing layer through van der Waals forces, strengthening the interfacial bonding between the hole transport layer and the perovskite light-absorbing layer and improving the mechanical strength of the overall perovskite cell structure.
[0036] Furthermore, compared to the hole transport material Spiro-OMeTAD in the prior art, it has a high defect density, poor stability, and is expensive, and it is often necessary to add additional modifying components to improve device efficiency. The hole transport material of the hole transport layer of the exemplary embodiment of the present invention is formed by benzenesulfonate molecules doped with nickel oxide, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid, [6-(3,6-dimethoxy-9H-carbazole-9-yl)hexyl]phosphonic acid, without the need for additional modifying components, and has higher stability and cheaper price. At the same time, compared to the formal structure perovskite photovoltaic cell, the trans-structured perovskite photovoltaic cell is currently the mainstream. Therefore, the trans-structured perovskite photovoltaic cell of the exemplary embodiment of the present invention is more conducive to subsequent industrial development.
[0037] Furthermore, the hole transport layer of the exemplary embodiment of the present invention can improve the photoelectric conversion efficiency of the perovskite photovoltaic cell by simply doping benzenesulfonate into the hole transport material through the mutual synergy of the two, compared with the simple hole transport material. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The accompanying drawings illustrate exemplary embodiments of the present invention and, together with the description, serve to explain the principles of the present invention. These drawings are included to provide a further understanding of the present invention and are incorporated in and constitute a part of this specification.
[0039] Figure 1 is a schematic structural diagram of a perovskite photovoltaic cell according to an embodiment of the present invention;
[0040] Figure 2 1 is a schematic flow chart of a method for preparing a perovskite photovoltaic cell according to an embodiment of the present invention;
[0041] Figure 3 are the steady-state fluorescence spectrum test results of the perovskite photovoltaic cells prepared in various embodiments and comparative examples;
[0042] Figure 4 are the transient fluorescence spectrum test results of the perovskite photovoltaic cells prepared in various embodiments and comparative examples;
[0043] Figure 5 2 are IV curves of the perovskite photovoltaic cells prepared in various embodiments and comparative examples. DETAILED DESCRIPTION
[0044] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0045] It should be noted that, in the following embodiments, if specific conditions are not specified, conventional conditions or conditions recommended by the manufacturer shall be followed. Reagents or instruments used without manufacturer specified are all commercially available conventional products.
[0046] Before introducing the embodiments of the present invention, the following definitions are given for the relevant terms involved in the embodiments of the present invention:
[0047] In photovoltaic cells and other optoelectronic devices, fill factor (FF) measures the impact of internal resistance and electron loss on their performance. A characteristic of the current-voltage (IV) curve, fill factor represents the ratio of the maximum output power (ImVm) to the limiting output power (IscVoc), i.e., FF = ImVm / IscVoc.
[0048] The fill factor ranges from 0 to 1, with values closer to 1 indicating better performance. The fill factor is primarily determined by series resistance, shunt resistance, and PN junction characteristics. Increased series resistance, decreased shunt resistance, and the presence of defects and impurities in the PN junction all contribute to a smaller FF. Furthermore, the fill factor increases with the bandgap of the cell material.
[0049] Short Circuit Current Density (Jsc) refers to the current density per unit area generated by a photovoltaic cell in a short-circuit state. In the short-circuit state, the two electrodes of the photovoltaic cell are directly connected together without external load. Its value is expressed as the intercept on the vertical axis of the JV curve diagram, and the unit is mA / cm 2 Jsc is primarily affected by the incident light intensity and the material's absorption bandgap. The smaller the bandgap, the greater the ability to convert photons into electrical energy. Additionally, device thickness, the quality of each film layer, and carrier transport capacity all have an impact on Jsc.
[0050] Open-circuit voltage (Voc) refers to the voltage difference between the two electrodes of a photovoltaic cell when no load is connected. The specific value of open-circuit voltage is represented by the intercept length on the horizontal axis of the JV curve diagram, and its units are generally mV or V.
[0051] Perovskite materials have an ABX3 crystal structure, which is a typical cubic structure. In this structure, the A position is usually a large radius cation, such as methylammonium (MA + ), formamide (FA + ) or cesium (Cs + ) etc.; the B position is a smaller metal cation, such as lead (Pb2 + ) or tin (Sn 2+ ); X position is a halogen anion, such as iodine (I - ), bromine (Br - ) or chlorine (Cl - ).
[0052] Figure 1 Schematic diagram of the structure of a perovskite photovoltaic cell according to an embodiment of the present invention. Figure 1As shown, the perovskite photovoltaic cell of the exemplary embodiment of the present invention is a trans-structure, which has a conductive substrate, a hole transport layer ( Figure 1 The structure of a perovskite photovoltaic cell consists of a conductive substrate, an electron transport layer, a perovskite light-absorbing layer, an electron transport layer, and a metal electrode. The conductive substrate can be made of materials such as fluorine-doped tin oxide (FTO) or indium tin oxide (ITO); the electron transport layer can be made of titanium dioxide or tin dioxide, and the metal electrode can be made of gold or silver. The formal structure of a perovskite photovoltaic cell is as follows: a conductive substrate, an electron transport layer, a perovskite light-absorbing layer, a hole transport layer, and a metal electrode, arranged in the direction of incident sunlight.
[0053] The efficiency loss of trans-structured perovskite photovoltaic cells mainly occurs at the interface defects between the perovskite photovoltaic cell and the hole transport layer and electron transport layer. Most related technologies use passivators to modify the defects on the upper and lower surfaces of the perovskite to improve cell performance. For example, the passivator phenylethylamine (PEA) coordinates with defect sites such as lead ions or iodide ions on the perovskite surface through its single amino group, forming a stable chemical bond, thereby passivating the defects; the lone pair electrons on the sulfur atom of thiourea (TU) can coordinate with low-coordinated lead ions in the perovskite to form Lewis adducts, effectively passivating the defects; and the iodide ions in potassium iodide can interact with defect sites such as low-coordinated lead ions or iodine vacancies in the perovskite to form stable chemical bonds, thereby passivating the defects. These passivators usually bind to a single active binding site on the surface of the perovskite light-absorbing layer. The vertically arranged passivators may be densely stacked on the upper and lower surfaces of the perovskite, introducing unnecessary resistance between the perovskite light-absorbing layer and the charge transport layer, hindering the extraction and transportation of carriers.
[0054] Inserting a hole transport layer and an electron transport layer between the perovskite light-absorbing layer and the electrode can reduce energy level mismatch and promote carrier transport, injection or extraction. The hole transport materials in the hole transport layer in the related art, such as poly-[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), have low wettability and energy level mismatch, resulting in poor interface contact and insufficient hole extraction, and are not suitable for large-area manufacturing; 2,2',7,7'-tetrakis(N,N-dimethoxyphenylamino)-9,9'-spirobifluorene (Spiro-OMeTAD) has high defect density, poor stability, and is expensive, and often requires the addition of additional modified components to improve device efficiency; the corrosiveness and hygroscopicity of PEDOT:PSS are not conducive to the stability of the device, and PSS - The interfacial mixing region caused by ion self-doping affects the performance of the device.
[0055] The perovskite photovoltaic cell of this exemplary embodiment incorporates benzenesulfonate molecules into hole-transporting materials such as nickel oxide. This reduces the resistance between the perovskite light-absorbing layer and the hole-transporting layer, increases hole extraction efficiency, and improves the perovskite cell's photoelectric conversion efficiency. The benzenesulfonate molecules' inherent flat structure and the resulting van der Waals anchoring effect with multiple Pb sites on the perovskite light-absorbing layer contribute to enhanced stability and a simpler production process.
[0056] In some embodiments, the hole transport material may include nickel oxide, or may include carbazole derivatives, such as Meo-2PACz, Meo-4PACz, Meo-6PACz, etc., wherein the chemical name of Meo-2PACz is [2-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl]phosphonic acid, the CAS number is 2377770-18-6, and the molecular formula is C 16 H 18 The chemical name of NO5P;Meo-4PACz is [4-(3,6-dimethoxy-9H-carbazol-9-yl)butyl]phosphonic acid, CAS number is 2922526-56-3, and the molecular formula is C 18 H 22 NO5P; The chemical name of Meo-6PACz is [6-(3,6-dimethoxy-9H-carbazol-9-yl)hexyl]phosphonic acid. Its structure is similar to Meo-2PACz and Meo-4PACz, but the carbon chain length is longer.
[0057] In some embodiments, the mass ratio of the hole transport material to the benzenesulfonate is 10:(0.05-0.1).
[0058] For example, the hole transport material is nickel oxide powder, and the mass ratio of nickel oxide powder to benzenesulfonate is 10:0.05, 10:0.06, 10:0.07, 10:0.08, 10:0.09, 10:0.1, etc. Since the hole transport layer is formed on the conductive substrate by solution spin coating, the above ratio of the two can ensure that the benzenesulfonate dissolves well in the deionized water solution and avoids precipitation, while also preventing other adverse changes in the hole transport layer, such as excessive benzenesulfonate causing a decrease in the conductivity of the hole transport layer itself.
[0059] In the spin-coated solution, the sum of the mass concentrations of nickel oxide and benzenesulfonate after mixing is 3 to 15 mg / mL, for example, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL, etc. Within this solution concentration range, a hole transport layer with uniformity, moderate thickness, and high electrical performance can be formed, thereby maximizing the efficiency and stability of the perovskite photovoltaic cell.
[0060] In some embodiments, the benzenesulfonate may include one or more of halogenated benzenesulfonates, alkylbenzenesulfonates, nitrogen-containing heterocyclic substituted benzenesulfonates, amino- and amine-substituted benzenesulfonates.
[0061] For example, the halogenated benzenesulfonate includes at least one of sodium 4-chlorobenzenesulfonate and 2-amino-5-chlorobenzenesulfonate hydrochloride.
[0062] The alkylbenzene sulfonate includes at least one of sodium 4-isopropylbenzene sulfonate, 13-hydroxytridecyl 4-methylbenzene sulfonate, and 1-hexadecyl-3-methyl-p-toluene sulfonate.
[0063] The nitrogen-containing heterocyclic substituted benzenesulfonates include imidazole benzenesulfonates, such as 1-decyl imidazole p-toluenesulfonate, 1-hexyl-3-methyl imidazole p-toluenesulfonate, 1-propyl-3-methyl imidazole p-toluenesulfonate, 1-hexadecyl-2,3-dimethyl imidazole p-toluenesulfonate, 1-butyl-2,3-dimethyl imidazole p-toluenesulfonate, 1-octylimidazole p-toluenesulfonate, N-sulfonic acid butyl-3-methyl imidazole p-toluenesulfonate, 1-decyl-3-methyl imidazole p-toluenesulfonate, 1-allyl-3-methyl imidazole p-toluenesulfonate, 1-methyl imidazole At least one of imidazole p-toluenesulfonate, 1-vinyl-3-butylimidazole p-toluenesulfonate, 1,3-dimethylimidazole p-toluenesulfonate, 1-benzyl-3-methylimidazole p-toluenesulfonate, 1-butyl-3-methylimidazole p-toluenesulfonate, 1-decyl-2,3-dimethylimidazole p-toluenesulfonate, 1-dodecylimidazole p-toluenesulfonate, 1-vinyl-3-propylimidazole p-toluenesulfonate, 1-hexylimidazole p-toluenesulfonate, 1-octyl-3-methylimidazole p-toluenesulfonate, and 1-propyl-2,3-dimethylimidazole p-toluenesulfonate.
[0064] The nitrogen-containing heterocyclic substituted benzene sulfonate may include pyridine benzene sulfonate, for example, at least one of N-methylbenzothiazole p-toluene sulfonate, N-sulfonic acid butylpyridine p-toluene sulfonate, N-hexylpyridine p-toluene sulfonate, N-propyl sulfonic acid pyridine p-toluene sulfonate, 1-butylpyridine p-toluene sulfonate, N-octylpyridine p-toluene sulfonate, N-sulfonic acid butyl-3-methylpyridine p-toluene sulfonate, and 1-ethylpyridine p-toluene sulfonate.
[0065] The nitrogen-containing heterocyclic substituted benzenesulfonate may also include at least one of 3,3-dimethylazetidine-4-methylbenzenesulfonate, 3-phenylazetidine toluenesulfonate, piperidine-4-carboxylic acid benzyl ester p-toluenesulfonate, (S)-pyrrolidin-3-ol benzenesulfonate, 1-propyl-1-methylpyrrolidine p-toluenesulfonate, 1-propyl-1-methylpiperidine p-toluenesulfonate, and 1-butyl-1-methylpiperidine p-toluenesulfonate.
[0066] The amino and amine substituted benzenesulfonates may include at least one of benzylhydrazine p-toluenesulfonate, aminomalononitrile p-toluenesulfonate, ethylenediamine mono-p-toluenesulfonate, aminocaproic acid ethyl ester p-toluenesulfonate, and 2-aminocyclopropanecarbonitrile p-toluenesulfonate.
[0067] The benzenesulfonate may further include at least one of benzyl bromide p-toluenesulfonate, biguanide trioctylbenzenesulfonate, (tetrahydrofuran-2-yl)methyl-4-methylbenzenesulfonate, and L-hydroxyproline benzyl ester p-toluenesulfonate.
[0068] Optionally, the benzenesulfonate may include sodium 4-chlorobenzenesulfonate, and the hole transport material may include nickel oxide. When the hole transport layer is doped with sodium 4-chlorobenzenesulfonate having a small molecular structure, nickel oxide and sodium 4-chlorobenzenesulfonate produce a synergistic effect, which can improve the hole extraction ability.
[0069] Alternatively, the molecular weight of benzenesulfonate is less than or equal to 2kDa, for example, less than or equal to 1KDa, 0.8KDa, 0.5KDa, 0.3KDa, etc. Such as 4-chlorobenzenesulfonate sodium, benzyl bromide ammonium toluenesulfonate, 4-isopropylbenzenesulfonate sodium, 2-amino-5-chlorobenzenesulfonic acid hydrochloride, 1-butyl-3-methylimidazole toluenesulfonate, N-sulfonic acid butylpyridine toluenesulfonate, etc., the sulfonate anion in the above-mentioned benzenesulfonate is para-substituted by the benzene ring, and a symmetrical planar conjugated skeleton is constructed, and its sulfonate radical and the benzene ring form a coplanar arrangement, thereby optimizing the continuity of the hole migration channel, and can effectively improve the hole extraction ability. When the molecular weight of benzenesulfonate is less than or equal to 2kDa, it is a small molecule structure, which shows significant advantages in improving hole transport performance through molecular-level dispersibility, precise energy level regulation and interface defect passivation. However, the chain entanglement, energy level broadening and process complexity of macromolecules or polymers limit their application in efficient and stable perovskite devices, which is not conducive to improving the efficiency and stability of perovskite cells.
[0070] In some embodiments, the thickness of the hole transport layer ranges from 20 nm to 200 nm, for example, 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, etc. Within this thickness range, the hole transport layer can ensure the light transmission performance of the perovskite photovoltaic cell while ensuring hole transport and reducing carrier consumption.
[0071] An exemplary embodiment of the present invention further provides a stacked battery comprising a plurality of electrically connected photovoltaic cells, wherein at least one photovoltaic cell is the photovoltaic cell in the above embodiment.
[0072] For example, the conductive substrate may be conductive glass used in single-junction perovskite photovoltaic cells, or may be a crystalline silicon photovoltaic cell, an amorphous silicon photovoltaic cell, a thin-film photovoltaic cell, etc. in a stacked perovskite photovoltaic cell.
[0073] The beneficial effects of the stacked cell provided by the embodiment of the present invention are the same as the beneficial effects of the perovskite photovoltaic cell provided by the above embodiment, and will not be described in detail here.
[0074] Figure 2 FIG. 1 is a flow chart of a method for preparing a perovskite photovoltaic cell according to an embodiment of the present invention. Figure 2As shown, an exemplary embodiment of the present invention also provides a method for preparing a perovskite photovoltaic cell, comprising: providing a conductive substrate; forming a hole transport layer on the conductive substrate, the hole transport layer comprising a hole transport material and benzenesulfonate, wherein the hole transport material comprises one or more of nickel oxide, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid, and [6-(3,6-dimethoxy-9H-carbazole-9-yl)hexyl]phosphonic acid; and sequentially forming a perovskite light absorbing layer, an electron transport layer, and an electrode on the hole transport layer to obtain a photovoltaic cell.
[0075] Specifically, the preparation method of the perovskite photovoltaic cell includes:
[0076] Step 201: Provide a conductive substrate, wherein the conductive substrate may be FTO, ITO, etc., may be conductive glass used for single-junction perovskite photovoltaic cells, or may be crystalline silicon photovoltaic cells, amorphous silicon photovoltaic cells, thin-film photovoltaic cells, etc. in stacked perovskite photovoltaic cells.
[0077] Step 202: Form a hole transport layer on a conductive substrate, the hole transport layer comprising a hole transport material and benzenesulfonate, wherein the hole transport material comprises one or more of nickel oxide, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid, and [6-(3,6-dimethoxy-9H-carbazole-9-yl)hexyl]phosphonic acid; wherein the mass ratio of the hole transport material to the benzenesulfonate is 10:(0.05-0.1), and in the spin-coated solution, the sum of the mass concentrations of the nickel oxide and the benzenesulfonate after mixing is 3-15 mg / mL.
[0078] The manufacturer of nickel oxide powder is Liaoning Youxuan New Energy Technology Co., Ltd., and the manufacturer of sodium 4-chlorobenzenesulfonate is Aladdin Reagent Co., Ltd.
[0079] Nickel oxide powder and sodium 4-chlorobenzenesulfonate are dissolved in deionized water in a specific ratio, ultrasonically dispersed to form a spin coating solution, and the solution is applied to the ITO glass by spin coating in an air environment. The spin coating speed ranges from 1000 rpm to 4000 rpm, for example, 1000 rpm, 1200 rpm, 1400 rpm, 1600 rpm, 1800 rpm, 2000 rpm, 2300 rpm, 2600 rpm, etc.; the spin coating time ranges from 10 s to 30 s, for example, 15 s, 20 s, 25 s, etc.
[0080] After spin coating, the conductive substrate coated with the solution is annealed, wherein the annealing temperature ranges from 120° C. to 180° C., such as 130° C., 140° C., 150° C., 160° C., and 170° C., and the annealing time ranges from 20 minutes to 40 minutes, such as 25 minutes, 30 minutes, and 35 minutes. Under the above annealing conditions, the performance of the perovskite photovoltaic cell can be optimized.
[0081] After annealing, the hole transport layer was treated under UV and ozone conditions for another 30 min.
[0082] Step 203: Prepare a perovskite light absorbing layer on the hole transport layer by spin coating.
[0083] Specifically: (1) 97.40 mg of CsI, 193.50 mg of FAI, 1654.28 mg of PbBr2, and 484.05 mg of PbI2 were dissolved in 1 mL of N,N-dimethylformamide (DMF) / dimethylsulfoxide (DMSO) (volume ratio of 4:1) and stirred at room temperature for 4 h to obtain a perovskite precursor solution;
[0084] (2) The precursor solution was spin-coated onto the hole transport layer. The spin-coating process was as follows: first, spin-coating at a speed of 1000 rpm for 20 seconds, then spin-coating at a speed of 4000 rpm for 30 seconds. In the 20th second of the second spin-coating step, 100 μL of ethyl acetate antisolvent was added. After spin-coating, the solution was annealed at 100 °C for 20 minutes to obtain a perovskite light-absorbing layer.
[0085] (3) Prepare an electron transport layer on the perovskite light absorbing layer.
[0086] Fullerene (C60) and bathocuproine (BCP) are sequentially deposited on the perovskite light-absorbing layer by a deposition device. The thickness of C60 is 25nm to 30nm, such as 27nm, 29nm, etc.; the thickness of BCP is 5nm to 10nm, such as 6nm, 7nm, 8nm, 9nm, etc., and the deposition rate is For example, wait.
[0087] Specifically, the evaporation equipment is used in sequence The electron transport layer can be obtained by evaporating C60 with a thickness of 25 nm and BCP with a thickness of 6 nm at a rate.
[0088] (4) Deposit metal electrodes on the electron transport layer at a deposition rate of
[0089] Specifically, the electron transport layer is deposited by evaporation. By evaporating Ag with a thickness of 120 nm at a rate, a perovskite photovoltaic cell can be obtained.
[0090] The following are some examples of the preparation of perovskite photovoltaic cells, and representative perovskite photovoltaic cells are selected for performance analysis.
[0091] Example 1
[0092] Step 1: Use glass cleaner, deionized water, acetone, and anhydrous ethanol to ultrasonically clean the ITO conductive glass, and then blow it dry with a nitrogen gun.
[0093] Step 2: Treat the conductive glass under UV-ozone conditions for 30 minutes.
[0094] Step 3: Spin-coat the hole transport layer on the ITO glass.
[0095] 10 mg of nickel oxide powder and 0.05 mg of sodium 4-chlorobenzenesulfonate were dissolved in 1 mL of deionized water, then ultrasonicated for 15 min, and then spin-coated onto ITO glass in an air environment at a spin coating speed of 2000 rpm for 30 s. After spin coating, it was annealed at 150 ° C for 30 min to obtain a hole transport layer.
[0096] Step 4: Treat the hole transport layer under ultraviolet ozone conditions for 30 minutes.
[0097] Step 5: Spin-coat the perovskite light absorbing layer on the hole transport layer.
[0098] 97.40mg CsI, 193.50mg FAI, 1654.28mg PbB r2 484.05 mg of PbI2 was dissolved in 1 mL of DMF / DMSO (volume ratio 4:1) and stirred at room temperature for 4 h to obtain a perovskite precursor solution;
[0099] The precursor solution was spin-coated onto the hole transport layer, specifically: first spin-coated at a speed of 1000 rpm for 20 seconds, then spin-coated at a speed of 4000 rpm for 30 seconds, and 100 μL of ethyl acetate antisolvent was added at the 20th second of the second spin-coating step. After spin-coating, it was annealed on a heating platform at 120°C for 20 minutes to obtain a perovskite light absorption layer.
[0100] Step 6: Prepare an electron transport layer on the perovskite light absorbing layer.
[0101] Use evaporation equipment in turn The electron transport layer was obtained by evaporating 25 nm thick C60 and 6 nm thick BCP at a rate of .
[0102] Step 7: Prepare a metal electrode on the electron transport layer.
[0103] The electron transport layer is deposited by evaporation By evaporating 120nm of Ag at a rate of , an inverse perovskite photovoltaic cell can be obtained.
[0104] Example 2
[0105] The difference between this embodiment and embodiment 1 is that:
[0106] The sodium 4-chlorobenzenesulfonate in step 3 was replaced by 2,4,6-trimethylpyridine p-toluenesulfonate.
[0107] Example 3
[0108] The difference between this embodiment and embodiment 1 is that:
[0109] In step 3, sodium 4-chlorobenzenesulfonate was replaced by benzylhydrazine p-toluenesulfonate.
[0110] Example 4
[0111] The difference between this embodiment and embodiment 1 is that:
[0112] The sodium 4-chlorobenzenesulfonate in step 3 was replaced by 1-decyl imidazole p-toluenesulfonate, and its mass was 0.1 mg.
[0113] Example 5
[0114] The difference between this embodiment and embodiment 1 is that:
[0115] The nickel oxide in step 3 was replaced by MeO-4PACz.
[0116] Comparative Example 1
[0117] The difference between this comparative example and Example 1 is only that:
[0118] The solution in step 3 does not contain sodium 4-chlorobenzenesulfonate.
[0119] Comparative Example 2
[0120] The difference between this comparative example and Example 1 is only that:
[0121] In step 3, nickel oxide was replaced by Spiro OMeTAD, and sodium 4-chlorobenzenesulfonate was replaced by 2,4,6-trimethylpyridine toluenesulfonate.
[0122] Comparative Example 3
[0123] The difference between this comparative example and Example 1 is only that:
[0124] The mass of sodium 4-chlorobenzenesulfonate in step 3 is 0.02 mg.
[0125] Comparative Example 4
[0126] The difference between this comparative example and Example 1 is only that:
[0127] The mass of sodium 4-chlorobenzenesulfonate in step 3 is 0.15 mg.
[0128] Table 1 Performance test results of perovskite photovoltaic cells prepared in various embodiments and comparative examples
[0129]
[0130]
[0131] Figure 5 : is the IV curve of the perovskite photovoltaic cell prepared in each embodiment and comparative example. Figure 5 As shown in Table 1, the photoelectric conversion efficiencies of Comparative Examples 3 and 4 are both lower than those of Example 1, indicating that a certain mass ratio of nickel oxide to benzenesulfonate can significantly improve photoelectric conversion efficiency. In other words, controlling the mass ratio of nickel oxide to benzenesulfonate within the range of 10:1 (0.05-0.1) in the present embodiments is beneficial for improving photoelectric conversion efficiency.
[0132] Compared with Comparative Example 1 in which only nickel oxide was used without benzenesulfonate, Example 1 had a photoelectric conversion efficiency increased by nearly 20%. Based on this, nickel oxide and benzenesulfonate have a synergistic effect.
[0133] In Example 1, the photoelectric conversion efficiency was improved by 15% compared to that of Comparative Example 2, where the hole transport layer used Spiro OMeTAD doped with 2,4,6-trimethylpyridine p-toluenesulfonate. Thus, the photoelectric conversion efficiency of the perovskite photovoltaic cell obtained by using nickel oxide and benzenesulfonate as the hole transport layer material was better than that of the perovskite photovoltaic cell obtained by using Spiro OMeTAD doped with 2,4,6-trimethylpyridine p-toluenesulfonate as the hole transport layer.
[0134] Figure 4 The transient fluorescence spectrum test results of the perovskite photovoltaic cells prepared in various embodiments and comparative examples are shown in FIG. Figure 4As shown, based on the transient fluorescence spectrum test results, the built-in software algorithm can calculate the corresponding decay time τ2. The decay τ2 caused by interface recombination in Examples 1 to 4 is 185.95ns, 263.61ns, 123.7ns, and 341.25ns, respectively, which are all greater than 106.09ns in Comparative Example 2 and 90.38ns in Comparative Example 1. The longer τ2 decay time indicates that the use of sodium 4-chlorobenzenesulfonate improves the defect state density between the hole transport layer and the perovskite light absorbing layer, which is beneficial to improving the fill factor of the perovskite photovoltaic cell.
[0135] Figure 3 Figure 2 is the steady-state fluorescence spectrum test results of the perovskite photovoltaic cells prepared in various embodiments and comparative examples. Figure 3 As shown, in Examples 1 to 4 and Comparative Example 2, the peak position after benzenesulfonate is incorporated into the Spiro OMeTAD or nickel oxide hole transport layer does not change and remains at 752 nm, proving that the incorporation of benzenesulfonate into the hole transport layer has no effect on the band gap of the perovskite light absorbing layer.
[0136] Continue as Figure 3 As shown in the figure, a lower photoluminescence (PL) peak intensity indicates a higher hole transport efficiency. Specifically, the PL peak intensity of Example 2 is lower than that of Comparative Example 2, and the PL peak intensity of Example 1 is the lowest. This indicates that doping benzenesulfonate, particularly sodium 4-chlorobenzenesulfonate, into nickel oxide improves the hole extraction efficiency of the hole transport layer, surpassing that of the hole transport layer doped with Spiro OMeTAD and that of undoped nickel oxide.
[0137] From the above, it can be seen that the perovskite photovoltaic cell provided by the exemplary embodiment of the present invention uses the hole transport layer formed by doping benzenesulfonate into nickel oxide in the reverse structure, and the current density is slightly improved, and the fill factor and cell photoelectric conversion efficiency are significantly improved.
[0138] It should be understood by those skilled in the art that the above embodiments are merely for the purpose of illustrating the present invention clearly, and are not intended to limit the scope of the present invention. For those skilled in the art, other changes or modifications may be made based on the above disclosure, and such changes or modifications are still within the scope of the present invention.
Claims
1. A perovskite photovoltaic cell, characterized in that: The invention comprises a perovskite light-absorbing layer and a hole transport layer stacked on one side of the perovskite light-absorbing layer, wherein the hole transport layer comprises a hole transport material and a benzenesulfonate, wherein the hole transport material comprises one or more of nickel oxide, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid, and [6-(3,6-dimethoxy-9H-carbazole-9-yl)hexyl]phosphonic acid.
2. The photovoltaic cell according to claim 1, characterized in that The mass ratio of the hole transport material to the benzenesulfonate is 10:(0.05-0.1); Preferably, the benzenesulfonate includes one or more of halogenated benzenesulfonates, alkylbenzenesulfonates, nitrogen-containing heterocyclic substituted benzenesulfonates, amino and amine substituted benzenesulfonates; Preferably, the molecular weight of the benzenesulfonate salt is less than or equal to 2 kDa.
3. The photovoltaic cell according to claim 1, characterized in that The benzenesulfonate comprises a sulfonic acid functional group containing a para-substituent on the benzene ring.
4. The photovoltaic cell according to claim 3, characterized in that The benzenesulfonate includes one or more of 4-chlorobenzenesulfonate, benzyl bromide p-toluenesulfonate, sodium 4-isopropylbenzenesulfonate, 2-amino-5-chlorobenzenesulfonic acid hydrochloride, 1-butyl-3-methylimidazole p-toluenesulfonate, and N-butylpyridinium sulfonate p-toluenesulfonate.
5. The photovoltaic cell according to claim 1, characterized in that The thickness of the hole transport layer ranges from 20 nm to 200 nm.
6. The photovoltaic cell according to claim 1, characterized in that The hole transport material includes nickel oxide, and the benzenesulfonate includes sodium 4-chlorobenzenesulfonate.
7. A laminated battery, characterized in that: The invention comprises a plurality of electrically connected photovoltaic cells, at least one of the photovoltaic cells is the photovoltaic cell according to any one of claims 1 to 6.
8. A method for preparing a perovskite photovoltaic cell, characterized in that: include: providing a conductive substrate; forming a hole transport layer on the conductive substrate, the hole transport layer comprising a hole transport material and a benzenesulfonate, wherein the hole transport material comprises one or more of nickel oxide, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid, and [6-(3,6-dimethoxy-9H-carbazole-9-yl)hexyl]phosphonic acid; A perovskite light absorption layer, an electron transport layer and an electrode are sequentially formed on the hole transport layer to obtain the photovoltaic cell.
9. The preparation method according to claim 8, characterized in that The mass ratio of the hole transport material to the benzenesulfonate is 10:(0.05-0.1); Preferably, the benzenesulfonate includes one or more of halogenated benzenesulfonates, alkylbenzenesulfonates, nitrogen-containing heterocyclic substituted benzenesulfonates, amino and amine substituted benzenesulfonates; Preferably, the molecular weight of the benzenesulfonate salt is less than or equal to 2 kDa; Preferably, the benzenesulfonate comprises a sulfonic acid functional group containing a para-substituent on the benzene ring; Preferably, the benzenesulfonate includes one or more of 4-chlorobenzenesulfonate, benzyl bromide p-toluenesulfonate, sodium 4-isopropylbenzenesulfonate, 2-amino-5-chlorobenzenesulfonic acid hydrochloride, 1-butyl-3-methylimidazole p-toluenesulfonate, and N-butylpyridinium sulfonate p-toluenesulfonate.
10. The preparation method according to claim 9, characterized in that When forming a hole transport layer on a conductive substrate, the method includes: preparing a hole transport material and benzenesulfonate into a solution and coating the solution on the conductive substrate; Preferably, the solution is coated on the conductive substrate by spin coating, the spin coating speed ranges from 1000 rpm to 4000 rpm, and the spin coating time ranges from 10s to 30s; and / or, The sum of the mass concentrations of the hole transport material and the benzenesulfonate is in the range of 3 mg / mL to 15 mg / mL; Preferably, after the solution is coated on the conductive substrate by a spin coating method, the preparation method further comprises: Annealing the conductive substrate coated with the solution, wherein the annealing temperature ranges from 120° C. to 180° C., and the annealing time ranges from 20 min to 40 min.
Citation Information
Cited By
3-carboxybenzenesulfonic acid sodium modified nickel oxide hole transport layer, trans-perovskite solar cell comprising same, and preparation method and application thereof
CN122476761A
3-carboxybenzenesulfonic acid sodium modified nickel oxide hole transport layer, trans-perovskite solar cell comprising same, and preparation method and application thereof
CN122476761B